ISLAMIC LEGAL REVIEW OF SINGLE-SIDED COMMISSION CHANGES BY SELLERS ON TIKTOK AFFILIATES: Analysis Based on the Principle of An-taradhin minkum - Lailatul Maghfirah; Shabarullah (JURISTA: Jurnal Hukum dan Keadilan, 2026)
This article analyses the validity of unilateral commission changes in the TikTok Affiliate Programme by focusing on the principle of antaradhin minkum as a substantive requirement of muamalah contracts. It relates it to the nature of affiliate agreements as standard digital agreements from a contract law perspective. This article takes a normative, conceptual approach to examine consent (ridha) in Islamic jurisprudence, the principles of agreement in civil law, and the construction of consent in digital contracts. To provide a practical context, this analysis is supported by limited empirical illustrations in the form of interviews with active affiliates, which are used as contextual illustrations (illustrative vignettes) rather than as a basis for legal determination. The analysis shows that changes to commissions after performance, without meaningful re-approval, can constitute formal consent, which does not fully reflect the substantive consent required in muamalah contracts. This condition can affect the validity of the contract and weaken legal protections for affiliates. The authors conclude that regulating digital muamalah practices is important to ensure that contractual consent does not stop at formalities and to ensure substantive consent and a more balanced legal relationship in platform-based affiliate schemes.